Qualidade sanitária e fisiológica de sementes de milho tratadas com extrato cambuci - Tronco, Vitória de Andrade (Universidade Federal de São Carlos, 2025)
Organic agriculture aims to produce healthy food in harmony with the environment and social security. For organic maize production, seed treatments are essential to maintain physiological and sanitary quality and prevent the spread of relevant phytopathogens in agricultural production fields. The control of these phytopathogens using plant extracts has been studied in the literature. Considering the potential antifungal activity of the secondary compounds produced by plants, the Cambuci (Campomanesia phaea) has this potential, as its leaves and fruits are rich in phenolic compounds, compounds with antifungal properties. The aim of this study was to evaluate the health and physiological quality of organic maize seeds treated with cambuci extract. Two plant extracts were prepared from different tissues of C. phaea species, fruit peel and leaves, in the following concentrations: 0%, 25%, 50%, 75% and 100%, and two ways of preparing the tissues, dry (the leaf or peel tissue was dried in an oven with forced air ventilation) and fresh (the peel or leaf tissue was not dried in an oven). The hydroalcoholic solvent extraction of the tissues was placed in a rotary evaporator to obtain a crude aqueous extract (100%) and diluted in water (to obtain concentrations of 25%, 50% and 75%) to be used in the application of the seeds. The seeds were evaluated for sanity by blotter test and for physiological quality by germination, germination speed index (GSI), seedling length, seedling dry matter mass and cold test. Each of the extracts used was evaluated for total phenolic compound content. The dry bark extract showed a higher germination percentage and germination speed index of maize seeds compared to the control, without affecting the biometric variables of the seedlings. The extract of fresh cambuci leaves, in which the highest levels of total phenolic compounds were observed, reduced the percentage of fungi of the genus Fusarium from the 25% concentration onwards. However, the 50% concentration of the fresh leaf extract had a phytotoxic effect on maize seeds, reducing germination by 10.7% compared to the control and the length of the aerial part of the seedlings by 19.46% compared to the control. The 75% concentration of the fresh leaf extract reduced the dry mass of the aerial part of the seedlings by 26.67% compared to the control. The fresh leaf extract at a concentration of 25% represents a promising strategy for treating corn seeds to control associated phytopathogens.
Sanitary and physiological quality of corn seeds treated with cambuci extract
Keywords: Campomanesia phaea; Zea mays L.; Plant extracts; Natural treatment; Extratos vegetais; Tratamento Natural; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA